Innovation of Blackening Labu Sayong (Jurnal Teknologi (Sciences & Engineering), 2013)
The blackening technique of Labu Sayong (LS) or clay pitcher commonly performed either traditionally or in modern way is by removing the clay pitcher from the firing area one by one after the firing temperature reached maturity at around 850°C to 900°C. A finding indicates a few improvements can be done such as reducing the time of transferring the clay pitcher to the paddy husks, reducing the fuel consumption, uniforming the blackened effect of Labu Sayong and reducing the defects ratio of Labu Sayong. The innovative is to add paddy husks or organic materials into the kiln as soon as the firing temperature reached maturity during the cooling process. The paddy husks will get burnt and produce a thick smoke. By closing all the burner port holes and chimney damper, the smoke will diffuses inside the firing chamber which gave the blackened effect to Labu Sayong. Based on the studies, the best temperature to add the paddy husks into the kiln is between 350°C to 700°C, depending on the size of the kiln. The innovation blackening Labu Sayong can overcome the disadvantages of the conventional blackening technique while increasing productivity without additional operation costs.